Case Report: Chronic Lymphocytic Leukemia With Recurrent Complement-Mediated Thrombotic Microangiopathy and C3 Glomerulonephritis - Ma, Tiantian; Wang, Hui; Su, Tao; Wang, Suxia (Frontiers in Medicine, 2022)
Chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL) is a monoclonal B cell lymphocytosis that produces nephrotoxic monoclonal immunoglobulin (MIg). However, the role of MIg in CLL and how it affects CLL patient survival are still unknown. Here, we report a case of MIg with renal significance (MGRS) associated with CLL. A 59-year-old Chinese woman complaining of abdominal pain, skin purpura, and typical soy-colored urine was admitted to the hospital for investigation. Laboratory tests revealed that she had microangiopathic hemolytic anemia, thrombocytopenia, acute kidney injury (AKI), and hypocomplementemia. She also reported cryoglobulinemia, thrombotic microangiopathy (TMA), and AKI 2 years previously. Peripheral blood smears at that time showed 4% schistocytes, a negative Coombs' test, and elevated lactate dehydrogenase (LDH). Based on a diagnosis of complement-mediated TMA, the patient was treated by plasmapheresis and achieved clinical disease remission. However, the serum hypocomplement 4 and cryoglobulinemia persisted. Further investigation showed elevated B lymphocytes and monoclonal serum IgMκ; however, the cryoprecipitate contained monoclonal IgMκ and polyclonal IgG, as well as immunoglobulins κ and λ. After plasmapheresis, her LDH, platelets, and complement 3 (C3) levels returned to normal. Biopsies of the bone marrow and an enlarged subclavicular lymph node revealed CLL/SLL. Renal pathological findings indicated significant arteriolar endothelial cells myxoid edema and glomerular endothelial cells swelling, however no thromboli, cryoglobulin formation and vasculitis were observed. We also found mild mesangial proliferative C3 glomerulonephritis and renal interstitial CLL cells infiltration. Collectively, these clinical and pathological manifestations were attributed to monoclonal IgMκ, which triggered C3 activation. MGRS associated with CLL was finally confirmed. Six cycles of rituximab, cyclophosphamide, verodoxin, and dexamethasone therapy were administered, after which she received ibrutinib. The patient experienced disease remission, and her serum C4 level returned to normal. Cryoglobulin and IgMκ were not detected. This is a special presentation of CLL/SLL with monoclonal IgMκ, which is a type of MGRS. Activation of the complement system by MIg led to TMA with C3 glomerulonephritis. Treatment for TMA and CLL/SLL should be initiated in a timely manner to improve patient prognosis.